Evaluation of a pilot emergency department linkage to care program for patients previously diagnosed with Hepatitis C. Issue 2 (8th December 2022) - Hyde, Zak; Roura, Raúl; Signer, Danielle; Patel, Anuj; Cohen, Jacob; Saheed, Mustapha; Brinkley, Sherilyn; Irvin, Risha; Sulkowski, Mark S.; Thomas, David L.; Rothman, Richard E.; Hsieh, Yu‐Hsiang
Abstract: There is a significant number of Emergency Department (ED) patients with known chronic hepatitis C virus (HCV) infection who have not been treated with directly acting antivirals. We implemented a pilot ED‐based linkage‐to‐care program to address this need and evaluated the impact of the program using the HCV Care Continuum metrics. Between March 2015 and May 2016, dedicated patient care navigators identified HCV RNA‐positive patients in an urban ED and offered expedited appointments with the on‐site viral hepatitis clinic. Patient demographics and care continuum outcomes were abstracted from the EMR and analysed to determine significant factors influencing linkage‐to‐care (LTC) and treatment initiation rates. The ED linkage‐to‐care program achieved a 43% linkage‐to‐care rate (165/384), 22% treatment rate (84/384) and 16% sustained virologic response rate (63/384). Significant associations were found between linkage‐to‐care and increasing age (OR = 1.03), Medicare insurance (OR = 2.21) and having a primary care physician (PCP) (OR = 4.03). For patients who were linked, the odds of initiating treatment were also positively significantly associated with increasing age (OR = 1.04) and having a PCP (OR = 2.77). For patients who initiated treatment, the odds of sustained virologic response were marginally associated with having a PCP (OR = 4.92).Our ED linkage‐to‐care program utilized care coordination to successfully link nearly half of approached HCV RNA‐positive patients to care. This design can be feasibly replicated by other EDs given limited non‐clinical training required for linkage‐to‐care staff. Adoption of similar programs in other EDs may improve the rates of LTC and treatment initiation for previously diagnosed HCV patients.